2023
DOI: 10.1038/s41467-022-35140-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting microporous functional living materials from protein-based core-shell microgels

Abstract: Living materials bring together material science and biology to allow the engineering and augmenting of living systems with novel functionalities. Bioprinting promises accurate control over the formation of such complex materials through programmable deposition of cells in soft materials, but current approaches had limited success in fine-tuning cell microenvironments while generating robust macroscopic morphologies. Here, we address this challenge through the use of core-shell microgel ink to decouple cell mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
0
18
0
2
Order By: Relevance
“…[41] Recently the average size of the filament generated using nozzles of different diameters was analyzed. [63] In this strategy, Gel/GelMA blend microgels with core-shell structure were used to produce the granular hydrogels by using a microfluidics chip, comprising three different solutions. A cell-loaded carboxymethylcellulose solution was flanked by the gelatin solution which is finally emulsified into droplets by the carrier oil.…”
Section: Printing Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] Recently the average size of the filament generated using nozzles of different diameters was analyzed. [63] In this strategy, Gel/GelMA blend microgels with core-shell structure were used to produce the granular hydrogels by using a microfluidics chip, comprising three different solutions. A cell-loaded carboxymethylcellulose solution was flanked by the gelatin solution which is finally emulsified into droplets by the carrier oil.…”
Section: Printing Resolutionmentioning
confidence: 99%
“…In this context, the water elimination effect was analyzed in a study that examined the extrusion and filament formation of PEG microgels. [ 63 ] The findings revealed that water is extruded prior to the filaments, which was linked to the water present in the interstitial spaces between the microgels. This suggests that the physical confinement of the syringe and nozzle leads to a tighter packing of the microgels and eliminates the interstitial water.…”
Section: Considerations For Granular Inks: Formulation and Challengesmentioning
confidence: 99%
“…However, it was only recently that these technologies have been applied to microbes. Thus far, the focus in microbiology has been quite different to that in human cell printing: rather than seeking to recreate microbial communities in their natural states, it was realised that microbes can be combined with abiotic matrices to create novel living materials (Duraj‐Thatte et al, 2021; González et al, 2020; Huang et al, 2019; Johnston et al, 2020; Lehner et al, 2017; Liu et al, 2018; Ou et al, 2022; Schaffner et al, 2017). Bacteria, in particular, can be mixed with biocompatible aqueous solutions that usually contain nutrients and chemical components to form a self‐supporting hydrogel.…”
Section: Figurementioning
confidence: 99%
“…They hypothesised that, when segregated, the species in question are not in direct competition for nutrients and so are better able to coexist and sustain production of betaxanthin. Another example uses this idea of spatial segregation to improve the production of 2‐phenylethanol (commonly used as rose scent) in a two‐species community comprising E. coli and Meyerozyma guilliermondii (Figure 1G) (Ou et al, 2022). The authors use E. coli to convert glucose into 1‐phenylalanine, which is then further transformed into 2‐phenylethanol by M. guilliermondii .…”
Section: Figurementioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 2, 2023. ; https://doi.org/10.1101/2023.05.02.539014 doi: bioRxiv preprint properties [5,6,7,8]. By cultivating two or more types of cells within a single system to replicate a natural symbiotic environment, it becomes possible to facilitate the exchange of energy, substances, and signals between different species [9,10,11]. This approach also enables the sharing of labor and metabolic processes, allowing for efficient partitioning of resources [12].…”
Section: Introductionmentioning
confidence: 99%